Analysis Management Risk of Extension Vasa Hotel Project Construction in Surabaya - Eka Nur Diana Saputry (NAROTAMA UNIVERSITY, Indonesia, 2022)
The complex and lengthy construction process can hinder the achievement of goals, especially for renovation projects that previously contained existing buildings. In the implementation of a construction project, there may be a risk that may be a risk that is greater than that detected or calculated by the company, if monitoring and control of the incident or situation is not carried out. Data collection was carried out by distributing questionnaires via google form and interviewing the parties involved in the project. The collected data will then be analyzed using probability impact analysis to determine the magnitude of the risk and factor analysis to determine the risk variables that have the most dominant influence on the development of the project. Risk assessment uses a Likert scale to determine the level of probability and impact. Furthermore, risk mapping is carried out to determine mitigation efforts for the dominant risk. There are 37 risk variables obtained in the results of interviews and literature studies. From this research, it is known that 1 risk is included in the criteria of low risk, 30 risks are included in the criteria of moderate risk (medium risk), and 6 risks are included in the criteria of high risk. The data is then projected into the risk treatment table so that the results are 1 acceptable risk, 30 unacceptable risk, 6 undesirable risks. Risk mitigation for the dominant risks that have been identified stems from location problems and difficult site access, implementation schedules that have to adapt to the operating hours of existing buildings, changed designs and material increases.